PENGARUH REALITAS JAMINAN, KUALITAS PELAYANAN YANG DIINTERMEDIASI KEPUASAN MEMBER TERHADAP LOYALITAS MEMBER PADA PRODUK TUPPERWARE - Kurniasih Yunita Sholichah Khusniyatus; Suwardi . (Value Added : Majalah Ekonomi dan Bisnis, 2021)
ABSTRACTThe purpose of this study was to describe and analyze the effect of realityassurance, service quality mediated by member satisfaction on Member Loyalty onTupperware Products in West Semarang. The population in this study were users ofTupperware products in West Semarang. A total of 120 respondents were used assamples. Data were collected by distributing self-administered questionnaires usingStructural Equation Modeling (SEM) analysis on Amos.This analysis is used to see the direct and indirect effects between variables.The results of this study indicate that the Reality of Guarantee does not have a directinfluence on Member Loyalty. However, Service Quality towards Member Loyaltythrough Member Satisfaction as an intermediary variable. In addition, the results ofthis study indicate that indirectly member satisfaction cannot mediate the reality ofguarantees for member loyalty. Similarly, the quality of service to member loyalty.